Postur Maritim Indonesia: Pengukuran Melalui Teori Mahan - Lillyana Mulya (Lembaran Sejarah, 2013)
This paper examines the debate in 1941 between Dutch historian J.C. van Leur and Verhoeven on the so-called Mahan Theory of the sea power of the East Indie Company (Vereenigde van OostIndie Compagnie, VOC). Alfred Thaye Mahan, an American maritime historian of the nineteenth century, inserted the idea of a seapower state, which implied that the United Kingdom was an ideal maritime state for the strong structure and effcient work of its sea power. Verhoeven used Mahan’s category of seapower to suggest that the VOC was a naval power of the seventeen century. However, Leur criticized Verhoeven saying that he had missed to address the element of the period the term naval power began to be accepted as a theoretical category. This paper argues that the debate between Leur and Verhoeven is relevant today as to re-consider the concept of archipelagic country, wawasan nusantara, that Indonesia has adopted so far.